Effect of Propolis on Diet-Induced Hyperlipidemia and Atherogenic Indices in Mice - Nada Oršolić; Irena Landeka Jurčević; Domagoj Đikić; Dunja Rogić; Dyana Odeh; Vedran Balta; Eleonora Perak Junaković; Svjetlana Terzić; David Jutrić (MDPI AG, 2019)
Obesity, a major health problem worldwide, is associated with increased cardiovascular risk factors, such as dyslipidemia, glucose intolerance, and hypertension. We investigated the antioxidative capacity of the ethanol extract of propolis (EEP) and its effect on the lipid profile, the hepatorenal function, and the atherogenic indices in mice fed with a high-fat diet (HFD). EEP (50 mg/kg) was given orally to mice for 30 days. After the treatments, levels of the serum total triglyceride and cholesterol, the high density lipoprotein (HDL-c) and low density lipoprotein (LDL-c) cholesterols, the serum enzymes, and the metabolites were measured, and atherogenic indices [atherogenic index of plasma (AIP); cardiac risk ratio (CRR); cardioprotective index (CPI); atherogenic coefficient (AC)] were calculated and compared with the antioxidant, the reducing power, the radical-scavenging, and the chelating activity of EEP. The HFD diet with EEP significantly reduced the negative lipid profile and lowered AIP, CRR, and AC and increased CPI in animals on a HFD. In addition, EEP reduced the weight of mice and lipid accumulation in the liver, and it had significant in vitro antioxidative activities. The EEP possesses anti-hyperlipidemic and antioxidant activity and exhibits protective action on the cardiovascular system and hepatorenal functions. Our results contribute towards the validation of the traditional use of propolis as a food supplement in aiding hyperlipidemic disorders.